Banana collecting mission in the Autonomous Region of Bougainville (AROB), Papua New Guinea. - Sardos, J.; Paofa, J.; Janssens, S.; Sachter-Smith, Gabriel L.; Rauka, G.; Roux, N. (2017)
Papua New Guinea (PNG), including neighbouring islands, is a recognized centre of diversity and potentially a domestication centre for banana (Christoleva et al. 2016; Lebot 1999; Sardos et al. 2016; Volkaert, 2011). IBPGR and QDPI (current DAF) in co-operation with the PNG Department of Agriculture and Livestock (current NARI) and supported by INIBAP (current Bioversity International), organized 4 collecting missions to mainland PNG and the Bismarck Archipelago in 1988-1989. In total, these missions allowed the collection of 264 wild and cultivated accessions out of which 86% appeared to be original genotypes (Arnaud and Horry 1997). The collected accessions were sent to both the National Banana Germplasm Collection at Laloki, Port Moresby and to the International Transit Centre (ITC) in Belgium for conservation purpose. They were also characterized and evaluated at the QDPI South Johnstone Research Station in Australia. Since 1994 and the signature of an agreement between Bioversity and FAO, all the germplasm conserved in the ITC, including the PNG material, is available to all on the understanding that it remains on the public domain. Therefore, more than 25 years after the PNG missions, 230 of the accessions collected in PNG are still conserved in-vitro in the ITC. Over the years, the PNG accessions constituted and still constitute significant and valuable resources for breeders and researchers and contributed to significantly improve our knowledge and perception of banana diversity and diversification. The Pacific region is known to host important levels of genetic diversity of a wide range of crops including bananas. Numerous crop collections have been performed in the past in an attempt to bring together these different resources into national or regional ex-situ collections. However, environmental hazards are numerous in the region (earthquakes, tsunamis, drought, hurricanes…) and local agricultural systems often appear more resilient in face of hazards than conventional ex-situ collections.